Trans-Synaptic Spread of Amyloid-β in Alzheimer's Disease: Paths to β-Amyloidosis. (24th December 2017) - Pignataro, Annabella; Middei, Silvia
Abstract : Neuronal activity has a strong causal role in the production and release of the neurotoxic β -amyloid peptide (A β ). Because of this close link, gradual accumulation of A β into amyloid plaques has been reported in brain areas with intense neuronal activity, including cortical regions that display elevated activation at resting state. However, the link between A β and activity is not always linear and recent studies report exceptions to the view of "more activity, more plaques." Here, we review the literature about the activity-dependent production of A β in both human cases and AD models and focus on the evidences that brain regions with elevated convergence of synaptic connections (herein referred to as brain nodes) are particularly vulnerable to A β accumulation. Next, we will examine data supporting the hypothesis that, since A β is released from synaptic terminals, β -amyloidosis can spread in AD brain by advancing through synaptically connected regions, which makes brain nodes vulnerable to A β accumulation. Finally, we consider possible mechanisms that account for β -amyloidosis progression through synaptically linked regions.